In Defense of Monopoly : How Market Power Fosters Creative Production - McKenzie, Richard B.; Lee, Dwight R.; Project Muse. (Ann Arbor : University of Michigan Press, 2008)
In Defense of Monopoly offers an unconventional but empirically grounded argument in favor of market monopolies. Authors McKenzie and Lee claim that conventional, static models exaggerate the harm done by real-world monopolies, and they show why some degree of monopoly presence is necessary to maximize the improvement of human welfare over time. Inspired by Joseph Schumpeter's suggestion that market imperfections can drive an economy's long-term progress, In Defense of Monopoly defies conventional assumptions to show readers why an economic system's failure to efficiently allocate its resources is actually a necessary precondition for maximizing the system's long-term performance: the perfectly fluid, competitive economy idealized by most economists is decidedly inferior to one characterized by market entry and exit restrictions or costs.
"The wretched spirit of monopoly" -- Deadweight-loss monopoly -- Monopoly as a coordination problem -- Welfare-enhancing monopolies -- Locked-in consumers -- Monopoly prices and the client and bonding effects -- The monopsony problem -- The NCAA: a case study of the misuse of the monopsony and monopoly models -- Monopoly as entrepreneurship -- Property and monopoly -- Summing up.
Description based on print version record.
Keywords: Production; Monopoles; Production (Economic theory); Monopolies; Business & Economics / Economics / Theory; Monopolies; monopolies; Production; Monopoles; Production (Economic theory); Monopolies; Electronic books